Joint Venture Agreement yang Komprehensif Sebagai Sarana Perlindungan Hukum Dalam Kegiatan Foreign Direct Investment (FDI) di Indonesia - Bangun, Michael Hagana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Joint venture agreements are subject to civil law, then their formation must meet the provisions of the Treaty Law as regulated in the Civil Code. These provisions are generally cast in the form of agreement clauses, which serve to guarantee that each party acquires rights and performs obligations in accordance with the agreement with explicit legal protection. In practice, however, there are still various legal issues and potential risks that arise in the implementation of a joint venture between foreign and local investors. This paper is aimed at knowing the role of joint venture agreements in the establishment of joint venture companies as investment protection in Indonesia is reviewed from the legislation regulations with the intention and purpose of providing investment protection for both foreign and national parties. Second. To know the regulation of foreign direct investment (FDI) in the form of joint venture companies in Indonesia. The research is descriptive in nature using a type of normative legal research method, i.e. conducted in a systematic and comprehensive way describing library studies by examining legal materials related to the object of study. The results of this study confirm that joint venture agreements play a strategic role in guaranteeing legal protection over investments, both for foreign and national parties. Synchronization between the joint venture agreement and the establishment deed of the Limited Liability Company authorized by the Government is an important condition for ensuring legal certainty in the implementation of the investment. Should there be any inconsistencies or contradictions between the contents of the joint venture agreement and the company’s founding deed, such conditions could potentially give rise to legal disputes that could be detrimental to either party. In such a situation, settlement through an arbitration forum becomes an alternative when other non-litigation routes do not produce agreement.